A systematic review of functional outcome and quality of life following reconstruction of maxillofacial defects using vascularized free fibula flaps and dental rehabilitation reveals poor data quality. Issue 8 (August 2016) - Wijbenga, Johan G.; Schepers, Rutger H.; Werker, Paul M.N.; Witjes, Max J.H.; Dijkstra, Pieter U.
Summary: Background: Reconstruction and oral rehabilitation of segmental maxillofacial defects resulting from ablative surgery is commonly achieved by osteocutaneous vascularized free fibula (VFFF) transplantation combined with implant-supported dental prostheses. We systematically reviewed the literature regarding impact of oral rehabilitation with or without dental implants on functional outcome and quality of life (Qol) following reconstruction of such segmental maxillofacial defects with VFFF. Methods: This systematic review was performed according to the PRISMA guidelines. A literature search was conducted using the databases of Cochrane, MEDLINE and EMBASE. Relevant search terms for maxilla or mandible, reconstruction with VFFF, and oral rehabilitation were used. Two reviewers independently assessed the publications using eligibility and research quality criteria (MINORS). Results: In total, 554 unique publications were found. After scrutinization, 2 prospective studies and 8 retrospective case-series without comparison were left for ultimate analysis. Quality ranged from 44% to 88% of the maximum score. Overall survival rate of the VFFF was 99% and the survival rate of dental implants was 95%. Speech intelligibility and overall aesthetic outcome were 'good' to 'excellent'. No statistically significant changes in QoL were found. Methods to measure functional outcome varied strongly, making pooling impossible. Conclusions: Oral rehabilitation with implant-supported dental prostheses after reconstruction of segmental maxillofacial defects with VFFF results in good to excellent speech intelligibility and aesthetics. Results are probably positively biased by the retrospective nature of the studies. In future prospective research, functional outcome measures should be addressed using standardized questionnaires and validated objective tests with adequate follow-up.